Preliminary Phytochemical Screening, Quantitative Analysis of Flavonoids from the Stem Bark Extract of Commiphora africana (Burseraceae) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2020)
The use of medicinal plants as a fundamental component of the traditional African health care system is perhaps the oldest, sustainable and most diverse of all therapeutic methods. Traditional medicinal herbal healers are, in many parts of rural Africa, the most readily accessible and inexpensive health resource available to the local population and, at times, the only surviving treatment. The Phytochemical analysis of Commiphora africana was carried out in three different organic solvents n-hexane, methanol and aqueous. Preliminary qualitative analysis revealed the presence of all the Phytochemicals analysed except anthraquinone and steroids. Quantitative phytochemical analysis showed that n-hexane fraction of Commiphora africana contains more phenolics and glycosides (6.2 ± 0.02, and 7.2 ± 0.1) respectively as compared to flavonoid (4.1± 0.03). High performance liquid chromatography (HPLC) of n- hexane extract of the plant using three standard flavonoids rutin, quercitin and gallic acid showed comparable RT values. From the calibration curve, it was compared and revealed the presence of more quercitin (60%) followed by gallic acid in a negligible amount. Quercetin has specific biological properties, which can enhance mental / physical efficiency and reduce the risk of infection.
Keywords: Commiphora Africana, flavonoids, HPLC, Phytochemicals, quercetin